2001
DOI: 10.1143/jjap.40.4581
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Internal Capacitors Based on Glass-Added Barium Titanate

Abstract: Barium–calcium–aluminum–borosilicate glass is added as a sintering promoter to reduce the sintering temperature of barium titanate. The dielectric properties of the glass-added barium titanate-based internal capacitors are investigated. The dielectric constants of the composites were found to increase with sintering temperature. A capacitance of about 2.3 nF/cm2 with the dissipation factor of 2.9% is obtained for a 20 wt% glass-added BaTiO3 internal capacitor after being cofired with low dielectric constant ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…However, in order to achieve BaTiO 3 with a high density and high dielectric constant, high sintering temperatures above 1300 • C is required. At present, adding glass with a low melting point is an effective and inexpensive way to reduce the sintering temperature of BaTiO 3 -based ceramics [3][4][5][6][7][8][9]. Jeon et al showed the effects of BaO-B 2 O 3 -SiO 2 glass additive on densification and dielectric properties of BaTiO 3 ceramics started from hydrothermally synthesized nano-sized BaTiO 3 powders (∼60 nm) [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in order to achieve BaTiO 3 with a high density and high dielectric constant, high sintering temperatures above 1300 • C is required. At present, adding glass with a low melting point is an effective and inexpensive way to reduce the sintering temperature of BaTiO 3 -based ceramics [3][4][5][6][7][8][9]. Jeon et al showed the effects of BaO-B 2 O 3 -SiO 2 glass additive on densification and dielectric properties of BaTiO 3 ceramics started from hydrothermally synthesized nano-sized BaTiO 3 powders (∼60 nm) [5].…”
Section: Introductionmentioning
confidence: 99%
“…After milling process followed the post-treatment process, nano-sized BaTiO 3 powders with non-aggregation characteristics could be obtained [15,16]. However, micron or submicron size glass powders with irregular morphology prepared by conventional melting process have been mainly used to decrease the sintering temperature of BaTiO 3 ceramic [3][4][5][6][7][8][9]. Nanosized glass powders have not been applied as the sintering agent for BaTiO 3 ceramics.…”
Section: Introductionmentioning
confidence: 99%